2021
DOI: 10.3390/agronomy11122502
|View full text |Cite
|
Sign up to set email alerts
|

Two-Stage Spatiotemporal Time Series Modelling Approach for Rice Yield Prediction & Advanced Agroecosystem Management

Abstract: A robust forecast of rice yields is of great importance for medium-to-long-term planning and decision-making in cereal production, from regional to national level. Incorporation of spatially correlated adjacent effects in forecasting models in general, results in accurate forecast. The Space Time Autoregressive Moving Average (STARMA) is the most popular class of model in linear spatiotemporal time series modelling. However, STARMA cannot process nonlinear spatiotemporal relationships in datasets. Alternately,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…By considering the MAPE values, a significant difference between the actual and forecasted values can be obtained by the DM test. The DM test was similarly used to compare the inter-combinational significance comparison between the models [45][46][47][48]. The results of the DM test revealed that in two sets (training and testing set) of data, the extreme learning machine intervention model performed better than all other models (Table 8).…”
Section: Discussionmentioning
confidence: 99%
“…By considering the MAPE values, a significant difference between the actual and forecasted values can be obtained by the DM test. The DM test was similarly used to compare the inter-combinational significance comparison between the models [45][46][47][48]. The results of the DM test revealed that in two sets (training and testing set) of data, the extreme learning machine intervention model performed better than all other models (Table 8).…”
Section: Discussionmentioning
confidence: 99%
“…In the second article, the authors predicted yields of rice grown in the most agriculturally intensive regions of India [8]. The two-step STRAMA (autoregressive moving av-erage) approach, referred to as STRAMA-II in this paper, was used to achieve the research objective.…”
Section: Papers In This Special Issuementioning
confidence: 99%
“…The AI and ML algorithms have been successfully applied in a wide range of agroenvironmental areas, including: plant-based [124,[129][130][131][132][133], pedological [134][135][136][137], and salinity-based [116,120,138] studies (Table 2). However, as soil salinization is commonly a highly complex and nonlinear variable [12], the data processed by AI and ML techniques could result in better outcomes vs. classical statistical methods in soil salinity classification and prediction.…”
Section: Exploration Of Salinization Processes By Artificial Intellig...mentioning
confidence: 99%
“…However, in some cases, ML (optimization) algorithms are employed to correct the assumptions of classical statistical models to obtain the robust predictions [ 123 , 124 ]. Additionally, for specific situations, neither linear nor nonlinear models provide better fitting; therefore, a combination of two or more algorithms/statistical models is needed, resulting in so-called hybrid or two-stage modeling approaches [ 116 , 125 , 126 , 127 , 128 , 129 ].…”
Section: Exploration Of Salinization Processes By Artificial Intellig...mentioning
confidence: 99%
See 1 more Smart Citation